THE SONNET TRADITION: CONTRIBUTIONS OF WYATT, SIDNEY, AND SPENSER (Ustozlar uchun, 2025)
This article explores the contributions of Wyatt, Sidney, and Spenser to the English sonnet tradition. It discusses how each poet transformed the Italian model into a distinctly English form. Wyatt introduced the Petrarchan sonnet, Sidney deepened its philosophical dimension, and Spenser created his own interlocking rhyme scheme. Together, they established the foundation for the later Shakespearean sonnet.